Applicability of Vesicular Formulation in the Delivery of Hydrophobic Drugs - Chaudhari, Gunjan (Asian Journal of Pharmaceutics (AJP), 2025)
The delivery of hydrophobic drugs has posed significant challenges in the field of pharmaceuticals due to their poor aqueous solubility and low bioavailability. Vesicular formulations, such as transferosomes and liposomes, have shown promise as effective medication delivery methods to address these issues. The application of vesicular formulations in improving the solubility, stability, and targeted delivery of hydrophobic medicines is summarized in this abstract. Because of their special bilayer structure, vesicular carriers can encapsulate hydrophobic medicines in their lipid or surfactant membranes, improving their solubility and bioavailability. Furthermore, vehicles can hold a variety of pharmacological compounds due to their flexibility. Phospholipid bilayers form liposomes, which have been thoroughly studied and could transport either hydrophilic or hydrophobic medications. In addition, interesting platforms for drug packaging and delivery are biosomes, which are made of non-ionized and transferosomes, which contain edge activators. Modifying vesicles with ligands or antibodies that identify receptors on target cells or tissues can enable the targeted administration of hydrophobic medicines. As a result, there are fewer side effects and better therapeutic results due to targeted medication distribution. To sum up, the distribution of hydrophobic medicines can be achieved through the diverse and efficient use of vesicular formulations. They offer solutions for enhancing drug solubility, stability, and bioavailability, as well as enabling targeted and controlled drug release. The continued exploration of vesicular carriers in drug delivery systems holds great promise for improving the therapeutic efficacy of hydrophobic drugs and expanding the possibilities of pharmaceutical science.